Mutation in the primer binding site of the type 1 human immunodeficiency virus genome affects virus production and infectivity. - Nagashunmugam, T (1992)
In an effort to understand the contribution of the primer-binding site (PBS) region to human immunodeficiency virus (HIV) replication, we have constructed a mutant HIV proviral DNA with an alteration in the 5' end of the PBS. The PBS mutant proviral DNA was characterized by transfection of the viral DNA into CD4+ and non-CD4+ target cells. The results indicate that mutation in the PBS reduced the level of viral particles released into the medium of transfected cells in comparison to wild-type proviral DNA. The viral particles were noninfectious upon transmission to established CD4+ cell lines and phytohemagglutinin-stimulated peripheral blood lymphocytes. Electron microscopic analysis of the transfected cells revealed no abnormalities in the structure of the virion directed by the mutant proviral DNA. Also, the protein and RNA contents of the mutant virions were similar to the wild type. The quantitation of intracellular viral structural protein in the transfected cells, however, indicated that the PBS mutation may have an effect on the assembly of viral particles in addition to completely abolishing reverse transcription of viral RNA into DNA. These results provide evidence that the PBS region of the viral genome has multiple functions in HIV-1 replication.